(untitled) (CIPEEX, 2025)
Obstructive Sleep Apnea (OSA) is a common and potentially serious disorder in which the individual experiences breathing pauses; it can occur in individuals with Chronic Kidney Disease (CKD), which consists of a gradual and progressive loss of blood filtration capacity. The objective of this study was to investigate, based on scientific publications, the occurrence of obstructive sleep apnea in patients with CKD. This is an integrative literature review that used the databases Virtual Health Library (VHL) and the U.S. National Library of Medicine Thesaurus (PubMed). Articles published in English, Portuguese, and Spanish, available in full text, addressing the proposed topic and published in the last five years were included. The search resulted in a total of 124 scientific publications, of which only 4 met the inclusion criteria. The studies showed a high prevalence of OSA in CKD patients. In summary, the integrative review highlighted the importance of early diagnosis and multidisciplinary care, as well as emphasizing the need for regular screening and continuous monitoring of patients undergoing dialysis, and the development of guidelines and recommendations for the diagnosis and treatment of OSA in CKD patients.